Global prevalence of visual impairment associated with myopic macular degeneration and temporal trends from 2000 through 2050: systematic review, meta-analysis and modelling - Fricke, Timothy R; Jong, Monica; Naidoo, Kovin S; Sankaridurg, Padmaja; Naduvilath, Thomas J; Ho, Suit May; Wong, Tien Yin; Resnikoff, Serge (British journal of ophthalmology, 2018)
PurposeWe used systematic review and meta-analysis to identify and assimilate evidence quantifying blindness and visual impairment (VI) associated with myopic macular degeneration (MMD), then derived models to predict global patterns. The models were used to estimate the global prevalence of blindness and VI associated with MMD from 2000 to 2050.MethodsThe systematic review identified 17 papers with prevalence data for MMD VI fitting our inclusion criteria. Data from six papers with age-specific data were scaled to relative age-dependent risk and meta-analysed at VI and blindness levels. We analysed variance in all MMD VI and blindness data as a proportion of high myopia against variables from the place and year of data collection, with a model based on health expenditure providing the best correlation. We used this model to estimate the prevalence and number of people with MMD VI in each country in each decade.ResultsWe included data from 17 studies comprising 137 514 participants. We estimated 10.0 million people had VI from MMD in 2015 (prevalence 0.13%, 95% CI 5.5 to 23.7 million, 0.07% to 0.34%), 3.3 million of whom were blind (0.04%, 1.8 to 7.8 million, 0.03% to 0.10%). We estimate that by 2050, without changing current interventions, VI from MMD will grow to 55.7 million people (0.57%, 29.0 to 119.7 million, 0.33% to 1.11%), 18.5 million of whom will be blind (0.19%, 9.6 to 39.7 million, 0.11% to 0.37%).ConclusionThe burden of MMD blindness and VI will rise significantly without efforts to reduce the development and progression of myopia and improve the management of MMD.